Pembiasaan Berwirausaha Untuk Seluruh Warga SMA N 1 Karangnunggal Melalui Aplikasi E Commerce SOS (SMANKA Online Shop) - Permana, Aji (LPPM Universitas Bina Bangsa, 2022)
GoEntrepreneurship is the attitude, soul and ability to create something new that is valuable and useful to yourself and others. Entrepreneurship is a mindset and spirit that is always positive or creative, empowering, creative, creative, humble, and seeks to increase income through business. Entrepreneurship occurs when someone tries to develop a new business or idea. Entrepreneurs are always dissatisfied with their performance. An entrepreneur is someone who can seize the opportunity to develop a business in order to improve the standard of living. Against this background, the author believes that entrepreneurship should be cultivated in schools with the aim of making it a habit, so that young entrepreneurs grow from an early age. The problem in this case study is the impact of e-commerce SOS (SMANKA online shop) on increasing entrepreneurship in schools. Based on our findings, we are very satisfied with the results, more than 1000 users, 512 partners, and 600 transactions registered on E-commerce SOS within 100 days of using e-commerce SOS. Students feel an advantage in personal character/ethics, online sales procedures, and store setup to attract buyers. This study is therefore of great value in preparing students for the future